DEALUMINATION AND CHARACTERIZATION OF ZSM - 5 AS CATALYST FOR GLYCEROL CONVERSION TO GLYCEROL MONOLAURATE - Didi Dwi Anggoro; Riko Rikardo Putra; Herawati Oktaviani; Lutfi Af’idatul Kamilah; FatmaTsaniya Chamdani (Reaktor, 2018)
Glycerol Monolaurate (GML) is a naturally occurring fatty acid widely utilized in food, cosmetics, andhomeopathic supplements. Glycerol is a compound glycerides, a byproduct of biodiesel production from the transesterification process. Glycerol is converted to glycerol derivative product that has more value as Glycerol Monolaurate (GML).GML is a naturally occurring fatty acid widely utilized in food, cosmetics, andhomeopathic supplements.One of the catalyst that had beenused is ZSM-5. Dealumination is used to change the acidity of the zeolite. This study consists of several stages, there are dealumination of zeolite ZSM-5 using H2SO4, drying at 110 ° C for 1 hour, Then calcination at a temperature of 550 ° C for 4 hours. Characterization catalyst to testing the acidity of the catalyst by absorption of ammonia and pyridine. Acidity of Zeolite is expressed in the mmol of ammonia or pyridine per gram of catalyst. Synthesis of monolaurate with dealuminated result are performed by GC-MS analysis, it’s to determine the molecular weight and to show a purity of Glycerol Monolaurate. Testing results obtained in the optimum conditions at dealumination temperature and dealumination time respectively are 40-60 0C and 2-5 hours. The dealumination variables are acid concentration, temperature and time of dealumination affecting ZSM-5 acidity and % yield of GML. The acidity affecting the yield% of Glycerol monolaurate produced Keywords :Glycerol, Glycerol Monolaurate, dealumination, ZSM - 5.